2009
DOI: 10.1111/j.1468-1293.2008.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in circulating markers of endothelial dysfunction in HIV‐infected patients during antiretroviral therapy

Abstract: ObjectivesAntiretroviral therapy (ART) in HIV-infected patients is associated with increased cardiovascular risk. Circulating markers of endothelial dysfunction may be used to study early atherogenesis. The aim of our study was to investigate changes in such markers during initiation of ART. MethodsIn 115 HIV-positive treatment-naïve patients, plasma lipids, E-selectin, soluble intercellular adhesion molecule 1 (sICAM-1), soluble vascular cell adhesion molecule 1 (sVCAM-1), tissue-type plasminogen activator in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
39
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
(33 reference statements)
9
39
0
2
Order By: Relevance
“…A longitudinal study comparing biomarkers in HIV-infected patients at ART initiation to two months and then 14 months into treatment demonstrated a normalization or significant reduction in levels of E-selectin, ICAM-1, VCAM-1 and CRP at the two month interval. These changes persisted up to 14 months except for E-selectin which did not change (Kristoffersen et al, 2009). Similar findings have been reported in other cohort studies, showing significant reductions in both vWF and VCAM-1 levels after six months following initiation of ART, with no demonstrable difference between PI and NNRTI containing regimes (Francisci et al, 2009).…”
Section: The Effect Of Art On Inflammatory Markers and Endothelial Dysupporting
confidence: 88%
“…A longitudinal study comparing biomarkers in HIV-infected patients at ART initiation to two months and then 14 months into treatment demonstrated a normalization or significant reduction in levels of E-selectin, ICAM-1, VCAM-1 and CRP at the two month interval. These changes persisted up to 14 months except for E-selectin which did not change (Kristoffersen et al, 2009). Similar findings have been reported in other cohort studies, showing significant reductions in both vWF and VCAM-1 levels after six months following initiation of ART, with no demonstrable difference between PI and NNRTI containing regimes (Francisci et al, 2009).…”
Section: The Effect Of Art On Inflammatory Markers and Endothelial Dysupporting
confidence: 88%
“…Therefore, we performed sequential measurements of C-IMT, arterial stiffness, and markers of endothelial function and inflammation in previously treatment-naive patients after the initiation of cART in a randomized clinical trial comparing a regimen of zidovudine/lamivudine/lopinavir/ritonavir (ZDV/3TC/LPV/r) with a nucleoside reverse-transcriptase inhibitor (NRTI)-sparing regimen of nevirapine/LPV/r (NVP/LPV/r). We previously reported that, during 24 months of follow-up, peripheral fat loss, visceral fat accumulation, and insulin resistance developed in the ZDV/3TC/ LPV/r arm, whereas lipid increases were greater in the NVP/ LPV/r arm [15,16]. We hypothesized that, against the background of these regimens having similar effects on the suppression of HIV and immune restoration, these different metabolic profiles might be reflected in different, mainly deleterious effects on the above-mentioned markers of cardiovascular disease risk.…”
mentioning
confidence: 97%
“…While modern cART efficiently suppresses HIV replication below the limit of detection in blood, promotes CD4 + T-cell recovery and stability, and decreases levels of inflammatory and immune activation markers [3,4], current evidence suggests that viral replication persists, likely within lymphoid organs, through cell-to-cell transmission, and/or through homeostatic proliferation [5][6][7]. Importantly, many markers of inflammation and immune activation are relatively nonspecific, and the precise events driving their production can be challenging to ascertain.…”
Section: Host-virus Interactionmentioning
confidence: 99%